university - Grigoryeva, Elena (project baikal, 2015)
Universities occupy a special place in the city’s life, the place where centuries-old traditions of the past meet the future. Universities keep their ancestral roots stretching back into the Middle Ages. University rooms and laboratories are the places where the future of science and society is built and discussed.The oldest Siberian University located in Tomsk was included in the City Charter as a city-forming enterprise. Other Siberian cities have not yet come to such deep comprehension of the role of universities. But who can doubt the significance and beneficence of this role?A complex and debatable process of reformation of the Russian higher education has been going on for several decades. Many things are perceived painfully. Irkutsk has been a student city for a long time and ranked second in the percentage of students among citizens. But recently we have lost Irkutsk High Military Aviation Engineering School, nearly lost the MIA High School. Pedagogical University has lost its status of university, and then its independence. Linguistic University has turned into a branch of Moscow University…Besides, external threats still exist and even grow. The lands and the buildings of universities are of keen interest among big businessmen, speculators and developers… Isn’t it the reason why the ideas to evacuate universities to suburban campuses arise increasingly frequently?What is the impact of dislocation of universities out of the city historical center? Does it make the city poorer and older? Or safer and more manageable? As usual, we tried to show the challenge and diversity of the main topic of the issue.
Keywords: university; city; Russia; higher education